VII a. pirmosios pusės kario kapo įkapių iš Lazdininkų (Kalnalaukio) kapinyno konservavimas - Beganskaitė, Rūta; Satkūnaitė, Sandra (Archaeologia Lituana, 2002)
The artefacts from the grave Nr. 73 were prepared and conserved in the archaeological department of the Lithuanian Art Museum P. Gudynas Restoration Centre. The artefacts reached the Restoration Centre strengthened in field conditions and packed carefully. Some of them were taken of with soil blocks.Laboratory conservation. Firstly the radiographs were made of iron weapons and artefacts in the soil blocks in order to learn the metal condition and exact position of the metal details.The iron artefacts (spearheads, scythe, knife, axe, riding bit, one-edged sword) were cleaned mechanically. After the cleaning the artifacts were treated with tannin solution in ethyl alcohol and consolidated with poly (butyl methacrylate) (PBMA) solution in xylene.Belt, scabbard adornments. The radiographs showed that metal condition was very bad: the metal alloys in many cases were fully mineralized, metal cord sometimes wasn’t fixed at all. The artefacts were carefully prepared following the radiograph view. The cleaning process was done under the microscope mainly. After the removal of surface corrosion crust the silver coatings were recovered on many brass details of the belt. After the cleaning artefacts consolidated with PBMA solution.Fibulas, rings. The metal condition was bad. The artefacts were carefully prepared, cleaned mechanically, recovered ornaments and silver coatings. After the cleaning artefacts consolidated with PBMA solution.The main material used in the process of cleaning and conservation was poly(butyl methacrylate) in xylene (5%, as consolidant) and in acetone (20%, as glue).